1998
DOI: 10.1086/301980
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Fibrosis of the Extraocular Muscles Type 2, an Inherited Exotropic Strabismus Fixus, Maps to Distal 11q13

Abstract: The extraocular fibrosis syndromes are congenital ocular-motility disorders that arise from dysfunction of the oculomotor, trochlear, and abducens nerves and/or the muscles that they innervate. Each is marked by a specific form of restrictive paralytic ophthalmoplegia with or without ptosis. Individuals with the classic form of congenital fibrosis of the extraocular muscles (CFEOM1) are born with bilateral ptosis and a restrictive infraductive external ophthalmoplegia. We previously demonstrated that CFEOM1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 20 publications
3
45
1
3
Order By: Relevance
“…fz encodes a seven-transmembrane helix containing protein necessary for binding Wnt ligands in the noncanonical Wnt signaling pathway (82) and has 10 human orthologs encoding frizzled class receptors, of which FZD4 is associated with exudative vitreoretinopathy (83). hbn encodes a transcription factor and has four human orthologs, of which PHOX2A has been associated with congenital fibrosis of extraocular muscles, a disorder that affects the muscles that control eye movement and position of the eyes (84,85). ktub has three human orthologs, of which TUB is associated with retinal dystrophy and TULP1 is associated with retinitis pigmentosa (86,87) and Leber congenital amaurosis (early-onset retinal dystrophy) (88, 89).…”
Section: Discussionmentioning
confidence: 99%
“…fz encodes a seven-transmembrane helix containing protein necessary for binding Wnt ligands in the noncanonical Wnt signaling pathway (82) and has 10 human orthologs encoding frizzled class receptors, of which FZD4 is associated with exudative vitreoretinopathy (83). hbn encodes a transcription factor and has four human orthologs, of which PHOX2A has been associated with congenital fibrosis of extraocular muscles, a disorder that affects the muscles that control eye movement and position of the eyes (84,85). ktub has three human orthologs, of which TUB is associated with retinal dystrophy and TULP1 is associated with retinitis pigmentosa (86,87) and Leber congenital amaurosis (early-onset retinal dystrophy) (88, 89).…”
Section: Discussionmentioning
confidence: 99%
“…2e). To determine the genetic cause of this CCDD, we conducted a genome-wide linkage screen and mapped CFEOM2 to chromosome 11q13, referred to as the FEOM2 locus (26). We constructed a physical map across the FEOM2 region and screened candidate genes within it (27).…”
Section: Cfeom2mentioning
confidence: 99%
“…We have identified this recessive disorder in consanguineous pedigrees, mapped it to the FEOM2 locus on 11q13, 9 and shown that it results from homozygous mutations in PHOX2A (ARIX). 10,11 PHOX2A encodes a homeodomain transcription factor essential to the development of the oculomotor and trochlear motoneurons in mice and zebrafish.…”
mentioning
confidence: 99%